2023
DOI: 10.3390/s23208639
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Disorder Recognition Based on Frontal EEG Signals and Deep Learning

Yanting Xu,
Hongyang Zhong,
Shangyan Ying
et al.

Abstract: Depressive disorder (DD) has become one of the most common mental diseases, seriously endangering both the affected person’s psychological and physical health. Nowadays, a DD diagnosis mainly relies on the experience of clinical psychiatrists and subjective scales, lacking objective, accurate, practical, and automatic diagnosis technologies. Recently, electroencephalogram (EEG) signals have been widely applied for DD diagnosis, but mainly with high-density EEG, which can severely limit the efficiency of the EE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…Another study presented in [47], reported the fact that there exists a relationship between the pre-frontal EEG electrodes and depression diagnoses. Furthermore, a sizable number of studies available in the literature have advocated the fact that frontal EEG electrodes play an important role in diagnoses of mental depressive disorders [48][49][50]. Therefore, Fp1, Fp2 and Fpz electrode signals have been extensively used for the diagnoses of depression.…”
Section: Eeg Signal Acquisitionmentioning
confidence: 99%
“…Another study presented in [47], reported the fact that there exists a relationship between the pre-frontal EEG electrodes and depression diagnoses. Furthermore, a sizable number of studies available in the literature have advocated the fact that frontal EEG electrodes play an important role in diagnoses of mental depressive disorders [48][49][50]. Therefore, Fp1, Fp2 and Fpz electrode signals have been extensively used for the diagnoses of depression.…”
Section: Eeg Signal Acquisitionmentioning
confidence: 99%